2017
DOI: 10.1177/1937586717728484
|View full text |Cite
|
Sign up to set email alerts
|

Macrocognition in the Healthcare Built Environment (mHCBE): A Focused Ethnographic Study of “Neighborhoods” in a Pediatric Intensive Care Unit

Abstract: Results from this study support the intricate link between macrocognitive interactions and space syntax constructs within the HCBE. These findings help increase understanding of how use of the framework of Macrocognition in the HCBE can improve design and support adaptation of interprofessional team practices, maximizing macrocognitive interaction opportunities for patient, family, and team safety and quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…To assess efficiency and workflow paired with the Planetree criteria of minimizing physical barriers to promote communication and compassionate interactions, the perception of increased walking post-move was contrary to expectations as the walking distances to the support rooms were relatively the same in the pre- as in the post-movement environment (Table 1). Similar findings regarding communication and physical barriers have been reported (O’Hara et al, 2018). The design intent of the 36-bed, 3 neighborhood floor plan was to bring all pathways in a small footprint through duplication of support rooms per 12-bed increments (Hua et al, 2012; Zadeh et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…To assess efficiency and workflow paired with the Planetree criteria of minimizing physical barriers to promote communication and compassionate interactions, the perception of increased walking post-move was contrary to expectations as the walking distances to the support rooms were relatively the same in the pre- as in the post-movement environment (Table 1). Similar findings regarding communication and physical barriers have been reported (O’Hara et al, 2018). The design intent of the 36-bed, 3 neighborhood floor plan was to bring all pathways in a small footprint through duplication of support rooms per 12-bed increments (Hua et al, 2012; Zadeh et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Physicians and nurses often differ in preferred workflow locations, with nurses proportionally favoring areas with higher targeted visibility toward patient beds and physicians favoring areas with generic visual connectivity and large open spaces ( Lu & Zimring, 2011 ). In a single-center study evaluating the PICU environment, O’Hara and colleagues (2018) concluded that maximization of visibility through the design of corner work zones can enhance team interactions and patient observation, creating opportunities for macrocognition and cognitive adaptation to complex situations. For severely ill patients admitted to the ICU, one study found a significantly higher hospital mortality rate in patients admitted to rooms with low visibility from the central nursing station ( Leaf et al, 2010 ).…”
Section: Icu Spatial Configuration and Amenitymentioning
confidence: 99%
“…There were, however, important exceptions to these trends. In addition to the Blennerhassett et al (2018) pre and post ward redesign study, there were other targeted studies with quantitative observation data that similarly did not produce specific conclusions about the environment from their observation methods (Anåker et al, 2018; Broom et al, 2019; Edgerton et al, 2010; Lu & Zimring, 2012; Miller & Keith, 1973; Newall et al, 1997; Pachilova & Sailer, 2020; Scrivener et al, 2019; Shannon et al, 2019; Shepley, 2002; Stahler et al, 1984), and there were some notable examples of exploratory studies with qualitative observation data which did produce specific conclusions (Eriksson et al, 2010; Hamilton, 2019; Karlsson et al, 2019; Kelley et al, 2011; O’Hara et al, 2018). The conclusions drawn from these exploratory studies tended to be layered, with multiple implications for hospital design.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 37% of the included publications were classified as drawing specific conclusions from their observation data (n ¼ 25), 43% were classified as drawing nonspecific findings (n ¼ 29), and 19% could not be determined (n ¼ 13). Of the 29 studies with nonspecific findings, 59% were unspecific about both the environment and behavior in their results (n ¼ 17), while 41% were specific regarding particular aspects of behavior but provided limited information in regard to the environment (n ¼ 12), as in the Blennerhassett et al (2018) observation data that similarly did not produce specific conclusions about the environment from their observation methods (Ana ˚ker et al, 2018;Broom et al, 2019;Edgerton et al, 2010;Lu & Zimring, 2012;Miller & Keith, 1973;Newall et al, 1997;Pachilova & Sailer, 2020;Scrivener et al, 2019;Shannon et al, 2019;Shepley, 2002;Stahler et al, 1984), and there were some notable examples of exploratory studies with qualitative observation data which did produce specific conclusions (Eriksson et al, 2010;Hamilton, 2019;Karlsson et al, 2019;Kelley et al, 2011;O'Hara et al, 2018). The conclusions drawn from these exploratory studies tended to be layered, with multiple implications for hospital design.…”
Section: Aims Addressed and Conclusion Drawnmentioning
confidence: 99%